The Relationship between Policy Design, Context, and Implementation in Integration Plans - Diem, Sarah (Education Policy Analysis Archives, 2012)
The decision handed down by the U.S. Supreme Court in Parents Involved in Community Schools v. Seattle School District No. 1 (2007) has forced school districts to begin thinking of new ways to integrate their schools without relying on race as the single factor in their assignment plans. While some school districts already have begun to implement race-neutral student assignments, others are just beginning the process and are looking to plans that have been able to maintain diversity despite the new limitations being placed on them. In an effort to understand factors critical in shaping racial and socioeconomic diversity in school districts given the new requisite limitations, this study examined the relationship between the design, context, and implementation of three different integration plans that rely on voluntary choice and socioeconomic status (SES). The findings suggest that geographic and political contexts matter in the shaping and adoption of integration plans based on voluntary choice and SES. Suggestions are offered to help maintain integration given the local sociopolitical context of the school districts.